Effect Of Independence, Auditor Experience, Task Complexity, And Time Budget Pressure On Audit Quality (Study On Surakarta, Yogyakarta, And Semarang KAP) - Ajiheri Anggara; Nugroho Wisnu Murti (Common Publisher, 2019)
The purpose of this study is to find out and provide empirical evidence of the significance of the influence of independence, auditor experience, task complexity, and time budget pressure on audit quality.This research is quantitative research. The population in this study were 74 auditors who worked in Public Accountants Office in Surakarta, Yogyakarta, and Semarang. The sampling technique used was convenience sampling and a sample of 58 auditors was obtained. The analysis technique consists of the classic assumption test, multiple linear regression analysis, t test, and R2 test. The results of testing the questionnaire using Test Validity and Reliability Tests that obtain valid and reliable results. The results of hypothesis testing indicate that the independence variable has a significant positive effect on audit quality. The auditor experience variable has a significant positive effect on audit quality. Task complexity variables have a significant positive effect on audit quality. Variable time budget pressure has a positive significant effect on audit quality. The R2 test results show that the Adjusted R Square value is 0.719. So that independence, auditor experience, task complexity, and time budget pressure can explain the level of audit quality by 71.9%, while 28.1% is influenced by other factors outside the research regression model.